The Genesis of the Gospel - Powell, J. Enoch (Journal for the study of the New Testament, 1991)
Internal evidence of a detailed textual character points to the first of the Synoptic Gospels, Matthew, having been the sole source of the other two and consequently prime evidence for the evolution of the contents. Analysis of Matthew, especially study of the recurrent phenomenon of duplication, discloses that an alternative to a basic text has been subsequently re-combined with it. This textual genesis reflects the rise and the eventual settlement of a crucial struggle between the pro-Gentile and pro-Jewish wings of the Christian Church over the identity of the Saviour and the mechanism of redemption. The basic text had marked affinities with the figure of Peter and reveals the existence of a Gentile church already possessing a fixed liturgy, the recognizable forerunner of the Catholic mass. The critical stage would fall most naturally after the Roman destruction of the Temple in AD 70.